'Just put it in perspective': the perception of sexual voyeurism and violence in Singapore evaluated through Facebook comments. Issue 1 (2nd January 2023) - Tan, Sarah
ABSTRACT: There is scant research about sexual violence and attitudes towards it in Singapore. This study seeks to understand if Singapore has a rape-supportive culture, by examining how sexual violence is conceptualized, including the rising phenomenon of technology-enabled sexual violence. Facebook comments in response to mainstream media reporting of a well-known case of sexual voyeurism in 2019 were analysed. The data suggest that gender role expectations create an environment in which sexual violence is enabled and male perpetrators are absolved, and in which women are blamed for failing to avoid victimization. Gendered expectations also shape normative understandings of sexual behaviours, though the digital elements of voyeurism complicate understandings of violence and harm, inviting conceptualization of violence that goes beyond the element of physical contact. Commentators who resisted gender norms and scripts discussed violence in terms of interference with one's autonomy. Generally though, the frames of reference discovered in this analysis drew heavily on state norms and narratives and it is the state that can play a critical role in shifting mindsets to combat sexual violence.